In-vitro Antioxidant and Cytotoxicity Studies of Annona squamosa Linn. - Biva, Israt Jahan; Vhuiyan, Md Mynol Islam; Saha, Moni Rani; Islam, Muhammad Shahidul; Sarwar, Shammy (Stamford Journal of Pharmaceutical Sciences, 2010)
n-Hexane, chloroform and methanol soluble extracts of the leaves of Annona squamosa were screened for their possible antioxidant activitiy by DPPH free radical scavenging and cytotoxicity by brine shrimp lethality bioassay. In DPPH radical scavenging assay, methanol soluble extract was found to be the most potent with an IC50 value of 103.5 μg/ml. The amount of total phenolics was also found to the highest in the methanol soluble extract (283.16 ± 8.90 mg/g), followed by chloroform soluble extract (216.90 ± 4.48 mg/g). Here BHT and ascorbic acid were used as standards with IC50 values 8.2 μg/ml and 25 μg/ml respectively. In the brine shrimp lethality bioassay, the most significant cytotoxicity was observed with chloroform soluble extract with an LC50 of 4.16 μg/ml where vincristine sulphate was used as standard (LC50 0.29 μg/ml). Key Words: Annona squamosa; DPPH; Folin-Ciocalteu Reagent; Phenolic Contents; Brine Shrimp DOI: 10.3329/sjps.v2i1.5813 Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 32-36